2009
DOI: 10.3390/ijerph6112822
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Co-Occurring Psychiatric Disorders on Retention in a Methadone Maintenance Program: An 18-Month Follow-Up Study

Abstract: We assess the influence of co-occurring psychiatric disorders on retention in 189 opioid dependent patients in a methadone maintenance treatment (MMT) and determine the incidence of psychiatric co-morbidity during an 18-month follow-up period. About 68.5 % were retained in the MMT. Neither co-occurring mental disorders (chi-square = 0.303, df = 1, p = 0.622) nor methadone doses [85 (88.9) vs. 79.2 (85) mg/day, p = 0.672] were related to retention. In the follow-up period 19 new diagnoses were made, mainly majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
31
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 27 publications
10
31
1
2
Order By: Relevance
“…This is a repeated finding in followup studies both in the general population and in substance users, whether in treatment or out of treatment (Astals et al, 2009;Grant et al, 2008;Martin-Santos et al, 2009). Consistent with the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC) study, being a woman was associated with a higher likelihood of developing a new non-SUD Axis I disorder; however, we did not find gender differences in the risk of incident SUD, whereas the NESARC study found a greater risk of incident drug dependence for men (Grant et al, 2008).…”
Section: Discussionmentioning
confidence: 69%
“…This is a repeated finding in followup studies both in the general population and in substance users, whether in treatment or out of treatment (Astals et al, 2009;Grant et al, 2008;Martin-Santos et al, 2009). Consistent with the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC) study, being a woman was associated with a higher likelihood of developing a new non-SUD Axis I disorder; however, we did not find gender differences in the risk of incident SUD, whereas the NESARC study found a greater risk of incident drug dependence for men (Grant et al, 2008).…”
Section: Discussionmentioning
confidence: 69%
“…Basic depression, anxiety, borderline personality disorder, and antisocial personality disorder are the most common psychiatric diagnoses among addicts (Astals et al, 2009;Roberts, Roberts, & Xine, 2007). Beck's theory of depression (Beck, Rush, Shaw, & Emery, 1979) proposes that difficult early life experiences can make an individual vulnerable to depression through the development of unhelpful core beliefs about the self, others, and the world.…”
Section: Introductionmentioning
confidence: 99%
“…In a Spanish sample of OD patients in a methadone maintenance programme (Astals et al, 2009), 32.3% had co-occurring mental disorders or a dual diagnosis (over half of them with Axis I disorders alone), and the prevalence seems to be increasing with time (Sanvisens et al, 2014).…”
Section: Introductionmentioning
confidence: 99%